2020
DOI: 10.1021/acs.molpharmaceut.0c00380
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Toxicity Study of Graphene-Based Tumor Cell Nucleus-Targeting Fluorescent Nanoprobes

Abstract: Graphene-based tumor cell nuclear targeting fluorescent nanoprobes (GTTNs) were synthesized in our laboratory as a kind of nanomaterial and showed good performance for both in vivo and in vitro imaging. GTTNs directly cross the cell membrane and specifically target the tumor cell nucleus via a cell membrane permeability targeting (CMPT) mechanism, which takes advantage of the increased permeability of the tumor cell membranes. GTTNs with a CMPT mechanism achieve high targeting efficiency in tumor tissues. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[ 14 ] With small size, non‐toxic, good biocompatibility, and fast metabolic rate, these CBNs have great potential to become excellent nanodrug carriers. [ 14b,15 ] We coated CBNs with Pluronic F127 and combined it with DOX to successfully prepare the CBNs‐Pluronic F127‐DOX (CPD) nanodrug delivery system. As result, the DOX targeting rate of CPD in tumor nucleus was as high as 36.78%, and the %ID/g in tumor tissue as high as 30.09%, resulting in tumor growth inhibition rate as high as 79.42 ± 2.83%, and greatly reduced the systemic side effects of DOX.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] With small size, non‐toxic, good biocompatibility, and fast metabolic rate, these CBNs have great potential to become excellent nanodrug carriers. [ 14b,15 ] We coated CBNs with Pluronic F127 and combined it with DOX to successfully prepare the CBNs‐Pluronic F127‐DOX (CPD) nanodrug delivery system. As result, the DOX targeting rate of CPD in tumor nucleus was as high as 36.78%, and the %ID/g in tumor tissue as high as 30.09%, resulting in tumor growth inhibition rate as high as 79.42 ± 2.83%, and greatly reduced the systemic side effects of DOX.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies focus on GFNs nuclear detecting techniques. In the biological imaging field, most research pays attention to safe application of fluorescent GFNs nuclear images rather than assessing genotoxicity of GFNs from an environmental toxicology point of view [135][136][137]. It is necessary to further optimize and develop detection techniques of GFNs in cells and organism tissues for a better understanding of genotoxicity.…”
Section: Detection Of Gfns In Cells and Organism Tissuesmentioning
confidence: 99%
“…In previous studies, we evaluated cytotoxicity in vitro and acute and subacute toxicity in vivo. 37,39 The results indicated that exposure to GTTNs showed little cytotoxicity, acute and subacute toxicity by CCK-8, behavior, organ coefficients, body weight, histological examinations, and biochemistry. It is well known that the male reproductive system is more susceptible to many exogenous materials compared with other organ systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These remarkable properties suggest that GTTNs have broad potential in tumor diagnosis and therapy. In previous studies, we evaluated cytotoxicity in vitro and acute and subacute toxicity in vivo . , The results indicated that exposure to GTTNs showed little cytotoxicity, acute and subacute toxicity by CCK-8, behavior, organ coefficients, body weight, histological examinations, and biochemistry. It is well known that the male reproductive system is more susceptible to many exogenous materials compared with other organ systems. , However, the toxicity of GTTNs to the male reproductive system and offspring development has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%